2010
DOI: 10.1175/2010jhm1191.1
|View full text |Cite
|
Sign up to set email alerts
|

Intra- to Multidecadal Variations of Snowpack and Streamflow Records in the Andes of Chile and Argentina between 30° and 37°S

Abstract: In a recent study the authors developed the first regionally averaged, transnational records of snowpack and streamflow for the Andes between 30° and 37°S using Chilean and Argentinean data. That study was mainly intended to evaluate the relationships between the interannual variations in the regional snowpack record and large-scale atmospheric variables and indices. Here the focus is on the main intra- to multidecadal variations in updated records of winter snowpack and mean annual river flows. River discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 20 publications
3
61
1
4
Order By: Relevance
“…A strong non-linearity in the behavior of long-term trends was observed considering the seasonal number of days with low flows [25], linked to the decadal behavior of the PDO. The cold (warm) phase of the PDO is linked to below (above)-average winter snowpacks and annual discharges [25,57]. Nevertheless, Boisier et al [5] have shown that the PDO accounts for half of the recent precipitation trends recorded in the Central Andes.…”
Section: Discussionmentioning
confidence: 99%
“…A strong non-linearity in the behavior of long-term trends was observed considering the seasonal number of days with low flows [25], linked to the decadal behavior of the PDO. The cold (warm) phase of the PDO is linked to below (above)-average winter snowpacks and annual discharges [25,57]. Nevertheless, Boisier et al [5] have shown that the PDO accounts for half of the recent precipitation trends recorded in the Central Andes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences in precipitation regime on both sides of the Andes, streamflow, which originates from snow and glacier melt in the Andes Mountains, shows a common seasonal regime for both slopes of the Andes (Masiokas et al 2013), common for energydriven hydrological systems. As a result, Argentinean and Chilean river flows in the MA show a strong mean intercorrelation over the snowmelt season (mean r 5 0.83; P , 0.001; 1954-2007 period).…”
Section: A Study Region and Climate Settingmentioning
confidence: 99%
“…The Mediterranean Andes region (MA; 308-378S) is located in the transition between two major macroclimate regions in South America, namely, the subtropical desert Andes to the north and the wet temperate Andes to the south (Lliboutry 1998). Several studies in the region have identified recent environmental changes characterized by 1) an increase of mean air temperature (10.258C decade 21 ) during the last three decades (1979Falvey and Garreaud 2009); 2) a reduction of the area covered by glaciers (Bown et al 2008;Masiokas et al 2009); 3) an increase of the 08C isotherm (Carrasco et al 2008); and 4) a negative, although not significant, precipitation trend since the beginning of the twentieth century (Vuille and Milana 2007;Le Quesne et al 2009;Quintana and Aceituno 2012). The rivers in the MA provide freshwater to around 10 million people on both sides of the Andes Mountains in Chile and Argentina (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations